Analisis Hukum Ekonomi terhadap Kebijakan Kelas Rawat Inap Standar (KRIS) dalam Upaya Mewujudkan Efisiensi dan Keadilan Jaminan Kesehatan Nasional - Muliani, Candra Wiwit; Suryono, Arief (Jurnal Locus Penelitian dan Pengabdian, 2025)
The Standard Inpatient Class (KRIS) policy is part of the reform of the National Health Insurance (JKN) system which aims to simplify inpatient services and eliminate class differentiation based on the amount of contributions. This policy is considered a step towards more equitable and equitable health services, and reflects the principle of distributive justice according to John Rawls' theory of justice as fairness. In addition, from an economic law perspective, KRIS has the potential to create efficiency in the use of health service resources. This study aims to analyze whether KRIS reflects the principles of justice and efficiency in the legal framework and public policy. The results of the study show that KRIS normatively supports equal access and distribution of services, although technical challenges such as the readiness of hospital infrastructure and the perception of participant dissatisfaction still need to be anticipated. Thus, KRIS is an important foundation in the formation of an inclusive, efficient, and equitable national health system.